Formulation and Production of Ethanol Extract Derived from Black Turmeric (Curcuma caesia Roxb) for use as an Antibacterial Hand Sanitizer Spray - Emma Zaidar Nasution; Faisal Mahdi Harahap (Talenta Publisher, 2024)
Formulation and production of an ethanol extract derived from black turmeric (Curcuma caesia roxb) for use as an antibacterial hand sanitizer spray were successfully performed. The method used is the maceration method with 96% ethanol solvent. Formulation of rimpang kunyit hitam (Curcuma caesia roxb) ethanol extract was formulated into four formulas: without extract, 10%, 8%, and 6% ethanol extract. The results showed that the ethanol extract of black turmeric rhizome with the phytochemical screening method contained flavonoids and alkaloids, which had antibacterial activity. Formulation of rimpang kunyit hitam ethanol extract in hand sanitizer spray with a concentration of 10% has a more significant inhibition zone compared to other concentrations, namely 9.9 mm in Escherichia coli and 9.8 mm in Staphylococcus aureus bacteria.